THE INFLUENCE OF PARTICIPATORY COMMUNICATION STRATEGY AND OBSERVATIONAL LEARNING ON PARTNER BEHAVIOR IN TELKOM MALANG'S PKBL PROGRAM - Sarasati, Fitri (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Partnership and Community Development Program is an activity of Corporate Social Responsibility (CSR) from PT. Telkom, Tbk. This activities are spread throughout Indonesia. In Java Island the largest partner is located in East Java, especially in Malang. The purpose of this study are: (1) to analyze the implementation of participatory communication strategy, (2) to analyze the influence of participatory communication strategy toward knowledge, attitudes and motivation of the assisted partners, and (3) to analyze the influence participatory communication strategy and learning observation of the behavior of the development partners. This research uses mixed method. The number of samples are 138 people chosen by a random sampling technique. The results showed that the implementation of participatory communication strategy has involved the partners in the process of identifying the problem, determining NOPS, and selecting the media and communication methods in PKBL Telkom activities. Participatory communication strategy positively affects the knowledge, attitude, and motivation of the assisted partners. The knowledge of the assisted partners, the attitudes of the assisted partners, the motivation of the assisted partners has a positive effect on the behavior of the assisted partners while the learning observation has a negative effect on the behavior of the development partners.